Immunoregulation through membrane proteins modified by reducing conditions induced by immune reactions. Issue 1 (16th January 2013) - Stegmann, Monika; Metcalfe, Clive; Barclay, A. Neil
<x xml:space="preserve">Abstract</x> Selected disulfide bonds in membrane proteins are labile and are thus susceptible to changes in redox potential and/or the presence of thiol isomerase enzymes. Modification of these disulfide bonds can lead to conformational changes of the protein that in turn may alter protein activity and function. This occurs in the entry of several enveloped viruses into their host cells, e.g. HIV, hepatitis C virus and Newcastle disease virus. Labile disulfide bonds are also important in platelet activation, cytokine signalling and in a variety of diseases including cancer and arthritis. In this review we will concentrate on recent advances in understanding the conditions that lead to disulfide bond reduction in membrane proteins and their effects in regulating immune function.